Achieving treatment goals in older breast cancer patients receiving neoadjuvant chemotherapy - Eda Caliskan Yildirim; Elif Atag; Huseyin Salih Semiz; Olcun Umit Unal; Mehmet Uzun; Suleyman Ozkan Aksoy; Merih Guray Durak; Aziz Karaoglu (Scientific Reports)
Abstract Neoadjuvant chemotherapy (NAC) is well-established for locally advanced breast cancer, even in the early stages, especially in HER2-positive and triple-negative cases. However, the effect of chronologic age on NAC response remains controversial. This study investigates the efficacy and outcomes of NAC in older patients with breast cancer, compared to a younger cohort, to address the current knowledge gap. 535 patients who received NAC followed by curative surgery from 2010 to 2021 were retrospectively analyzed. We evaluated breast and axillary downstaging, pathologic complete response (pCR), and post-treatment toxicities. Data were stratified by age, with patients aged 65 years and older representing the older group. Anthracycline-based chemotherapy was prevalent (97.6%) and favored younger patients who received a dose-dense anthracycline regimen (71.7% vs. 38.5%, p < 0.001). Surgical outcomes, breast and axillary downstaging, and the pathologic complete response showed no age-related differences. Grade 3–4 toxicity was higher in older patients (71% vs. 46.4%, p < 0.01). Older patients treated with NAC achieve comparable outcomes to younger patients, supporting personalized treatment. Chronologic age should not dictate treatment decisions, emphasizing the need for comprehensive evaluation for optimal geriatric patient care.